Biocontrol activity of Bacillus halotolerans strain Pl7 against Botryosphaeria dothidea causing apple postharvest decay and potential mechanisms - Yuan, Hongbo; Yuan, Mengjia; Shi, Bingke; Wang, Zhuoni; Huang, Tianxiang; Zhu, Jiahong; Hou, Hui; Wang, Li; Tu, Hongtao (Frontiers in Microbiology, 2023)
Apple ring rot, one of the most common apple postharvest diseases during storage, is caused by Botryosphaeria dothidea. Fungicide application is the most widely used method to control this disease, but the increasing environmental and food safety concerns greatly limit their use. The present study aimed to examine the biocontrol activity and underlying action mechanism of Bacillus halotolerans strain Pl7 against B. dothidea. The results revealed that B. halotolerans strain Pl7 exhibited strong inhibitory activity against B. dothidea by 69% in vitro. The culture filtrate of strain Pl7 possessed cellulase, β-1, 3-glucanase, protease activity and mediated the antifungal activity against B. dothidea. Further analysis demonstrated that culture filtrate of strain Pl7 could cause cell membrane permeabilization of B. dothidea. Apple fruit suffering from ring rot induced by a carbendazim (CBZ)-sensitive or -resistant B. dothidea isolate was much suppressed after being treated with strain Pl7, maintaining postharvest quality. The ability of strain Pl7 to swiftly colonize and thrive in apple fruit wounds was demonstrated by a re-isolation assay. Additional transcriptome studies of untreated and treated apple fruit with strain Pl7 revealed that strain Pl7 mostly changed the expression of genes functioning in plant secondary metabolite biosynthesis and plant-pathogen interaction. In light of these outcomes, the underlying antagonistic mechanism was investigated, and B. halotolerans strain Pl7 was identified as a promsing microbial biocontrol agent against apple postharvest decay.